Обзор методов биоиндикации и биотестирования для оценки состояния окружающей среды - Еремеева А. С. Алена Сергеевна; Донченко М. И. Марина Игоревна; Бучельников В. С. Виктор Сергеевич; Перегудина Е. В. Елена Владимировна; Азарова С. В. Светлана Валерьевна (Экология, 2015)
Заглавие с экрана